Evaluation of ecosystemic services in an unplanned city: The Quetzaltenango case - López Huertas, Mario Joaquín (2019)
The balanced growth between the natural and built environment is crucial for the sustainability of a society. With the current scenarios of the urban growth rate increasing in most of the cities around the world, the development of ecosystems that provide services to support cities becomes necessary. These services can range from economic processes with losses or profits to the perception of an inhabitant’s wellbeing. This research project assesses seven ecosystem services (ES) in the city of Quetzaltenango and analyzes the consumption of unplanned urban growth. The lack of knowledge, prioritization, land access, economic conditions, and adequate governance of regional and landscape planning are the main factors that those who are involved in makingdecisions regarding land use do not give importance to the ES. As a result, these actions produce natural environment deterioration represented by annual economic losses. In addition, this study presents hypothetical scenarios for an ecosystem recovery, leading urban development towards a natural-cultural symbiosis.